Odpowiedzi

2010-03-22T21:12:59+01:00
A) 3x+y=1
6x+2y=5

y=1-3x
6x+2(1-3x)=5

y=1-3x
6x-2-6x=5

y=1-3x
0=13 rownanie sprzeczne

b)4x-y=8 /*-2
8x-2y=16

-8x+2y=-16
8x-2y=16

0=0 rownianie tozsamosciowe

c)6x-5y=-5 /*-5
5x-6y=6 /*6

-30x+25y=25
30x-36y=36

-11y=61 /-11
y=-5 6/11

y=5 6/11
5x-6y=6

y=5 6/11
5x-6*(-5 6/11)=6

y=5 6/11
5x+33 3/11=6

y=5 6/11
5x=6-33 3/11

y=5 6/11
5x=

2 3 2
Najlepsza Odpowiedź!
2010-03-22T21:25:50+01:00
A) {3x+y=1
{6x+2y=5

y=1 - 3x
6x +2 * (1-3x) = 5
6x + 2 - 6x = 5
6x - 6x = 5-3
0=2 sprzeczne

b) {4x-y=8
{8x-2y=16

-y = 8 -4x \: (-1)
y= -8 + 4x

8x - 2*(-8 +4x) = 16
8x +16 - 8x = 16
8x - 8x =16 - 16
o=o tozsamosciowe

c) {6x-5y=-5
{5x+6y=6

6x = -5 + 5y \ :6
x = -5 +5y\6

5 * (-5 +5y)\6 + 6y = 6
-25 +25y \6 + 6y = 6 |*6
-25 + 25y +6y + 36
25y +6y = 36 +25
31y = 61 \: 31
y=2

6x - 5*2 = -5
6x -10 = -5
6x = -5 +10
6x = 5 \: 6
x = 5\6
1 1 1